2019
DOI: 10.1016/j.jen.2018.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Significant Coronary History and ECG Misinterpretation Are the Strongest Predictors of Undertriage in Prehospital Chest Pain

Abstract: Introduction: Appropriate prehospital (PH) triage of patients with chest pain can significantly improve outcomes in acute myocardial infarction (MI). We sought to explore how PH providers triage chest pain as high versus low risk and to evaluate the accuracy and predictors of their triage decision. Methods: This was a prospective, observational cohort study that enrolled consecutive patients with chest pain transported by emergency medical services (EMS) to 3 tertiary care hospitals in the US. EMS triage dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
(19 reference statements)
2
7
0
Order By: Relevance
“…This finding is shared with the findings by Faramand et al. (2019) in which EMS personnel's ECG interpretation competency was lower than that of hospital emergency nurses (Faramand et al., 2019). Similarly, the results of the study by Werner et al.…”
Section: Discussionsupporting
confidence: 80%
“…This finding is shared with the findings by Faramand et al. (2019) in which EMS personnel's ECG interpretation competency was lower than that of hospital emergency nurses (Faramand et al., 2019). Similarly, the results of the study by Werner et al.…”
Section: Discussionsupporting
confidence: 80%
“…Some characteristics of the ECG have a low sensitivity for a true infarction because the standard 10-second ECG is simply a snapshot of a very dynamic process [12,13,16]. Furthermore, the standard 12-lead ECG does not have posterior leads and can be easily misinterpreted [14,15]. Novel characteristics such as QRS-T angle on the 12-lead ECG have improved sensitivity and can overcome some of these other limitations [16].…”
Section: Discussionmentioning
confidence: 99%
“…Though AHA/ACC guidelines consider it reasonable to place leads over the posterior wall (V7-V9), it is not necessarily performed in clinical practice [2,14]. Lastly, the ECG is often misinterpreted by providers further leading to treatment delays [14,15]. Newer research has identi ed novel characteristics on the ECG related to UA/NSTEMI which have higher sensitivity and the potential to overcome these identi ed limitations [12,16].…”
mentioning
confidence: 99%
“…However, this is not the case quite frequently. A recent study found that 30% of myocardial infarction events were misclassified as low risk, with ECG misinterpretation responsible for half of the misclassifications [7]. Misdiagnosis is also a top concern expressed by cardiac patients [9].…”
Section: Introductionmentioning
confidence: 99%